Cognitive-Behavioral Differences Between Officials and Folks in China's Targeted Poverty Alleviation: An Evolutionary Game Theory Perspective - Chen, Zhi; Yang, Chao (Frontiers in Psychology, 2022)
China has historically eliminated absolute poverty and built a comprehensive well-off society through targeted poverty alleviation, at the end of which, however, many issues worthy of scholars' attention kept emerging. A significant one was cognitive-behavioral differences between officials and folks regarding the time, standards, and methods of removing the poverty hats. Officials strictly carried out targeted poverty alleviation work according to the criteria specified by the government. In comparison, folks who have reached poverty elimination standards were unwilling to take off their poverty hats after targeted assistance due to the fear of returning to poverty. To fully explain this phenomenon, this study analyzes the causes and solutions of cognitive-behavioral differences between officials and folks in China's targeted poverty alleviation from the perspective of Evolutionary Game Theory. The results show that bounded rational officials and folks will eventually be trapped in the prisoner's dilemma without exogenous factors' intervention. Furthermore, the study proposes that the government establish reasonable punishment, incentives, and supervision mechanisms to guide officials and folks and eliminate their cognitive-behavioral differences by investigating the influence of exogenous policy factors on the Evolutionarily Stable Strategy (ESS) of the official-folk game. This finding not only provides a reference for other developing countries to overcome absolute poverty, but also helps to consolidate and expand the achievements of poverty alleviation and effectively connect with rural revitalization.